PENERAPAN TEKNOLOGI PENGOLAHAN LIMBAH KELAPA SEBAGAI PUPUK ORGANIK DAN NATA DE COCO - Darma Bakti; Ridwansyah; Isman Nuriadi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Community service activities is one of the obligations that must be implemented by lecturer at the university sabagai one aspect of Tri Dharma Perguruan Tinggi. The activity was carried out by a Team of Community Service entitled "The Application of Coconut Waste Processing Technology as Organic Fertilizer and Nata de Coco" is a devotion activity involving two partners, namely Bakti Karya Farmer Group and Mekar Jaya Farmer Group are two groups of farmers who are active in cultivation and coconut cultivation in Desa Asahan Mati, Tanjung Balai Sub-district of Asahan Regency. Problems faced is the low quantity and quality of coconut production caused by the limited information about the culture culture of coconut cultivation, especially aspects of pest control and fertilization. In addition, the presence of coconut straw waste in the form of midrib and leaves and coconut water that is very large to be a problem because it has the potential to cause environmental pollution and become a pest of nests. . In order to solve the problems of both partners, this activity will be conducted in the form of lectures, discussions, practices and introduction of coconut chopping machine in the form of leaf and stem to be used as raw material of organic fertilizer, hybrid coconut seeds and coconut waste water treatment equipment as nata de coco . After the implementation of the dedication activity to the partner community has been able to make organic fertilizer bokashi by utilizing the waste of coconut plants by digging the compost cutting machine that introduced, the practice of hybrid coconut cultivation, and waste water treatment of coconut to nata de coco. The results of these activities can increase hybrid coconut production while maintaining environmental sustainability,